Board member perceptions of board effectiveness in public community colleges: an interpretative phenomenological analysis - Davis, Gwendelyn Finch, author; Anderson, Sharon K., advisor; Hall, Bruce, committee member; Hegeman, Diane, committee member; Quick, Don, committee member (Colorado State University. Libraries, 2015)
Many organizations have a governing board in place to assist in monitoring high level policy decisions and establishing organizational direction and goals. Studies have examined board members of different types of higher education institutions; however, the perceptions of public community college board members related to board effectiveness has not been studied. The current qualitative study, drawing upon Interpretative Phenomenological Analysis (IPA), addresses this gap in the literature by researching the lived experiences of seven public community college board members with two or more years of service related to board effectiveness in one western state. The findings resulted in four superordinate themes: personal development and engagement, board engagement, college commitment and engagement, and community engagement. Board effectiveness is demonstrated when board members are personally committed to fostering an environment that promotes and values board member development through participation in orientation program and ongoing board education. Board member development also promotes an understanding of the board's role and works to alleviate unhealthy personal or political agendas an individual may bring with them to the board. Participants highlighted the importance of building relationships with other board members and the CEO. By working together as a team, the board and CEO can focus on the college's mission and establishing the future direction for the college. Board effectiveness is also demonstrated through being involved in college activities and events and by ensuring the college is establishing board policies that ensure consistency in the board's operations for planning and decision making purposes. Community colleges have more of a local focus as compared to other organizations where effectiveness studies have been conducted. The findings of the current study deviated from previous board effectiveness studies independent, private colleges in the importance of the CEO's relationship with the board. The findings also diverged from the studies on public university board effectiveness related to community connections, with community colleges having a need for more of a local focus versus public universities needing to build stronger connection with state government. Effective community college boards embrace their responsibility to represent the community's interests in the college and to strengthening relationships with the public they serve. A common term throughout the findings of the current study is "engagement" with an emphasis on being actively involved in all aspects of boardsmanship. Effective board members are engaged in being oriented, educated, and developed as a board member, in working together as a team and with the CEO, in establishing and maintaining the college's mission and future direction, and in connecting with the communities and citizens served.
Keywords: board effectiveness; board of trustees; community college; governance; higher education; leadership